2023
DOI: 10.3390/medicina59050818
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Sleep Disturbances: A Literature Review of Clinical Evidence

Abstract: The need for adequate good quality sleep to optimally function is well known. Over years, various physical, psychological, biological, and social factors have been investigated to understand their impact on sleep. However, understanding the etiological processes that are involved in causing sleep disturbances (SD) as impacted by stressful phases such as pandemics has not been well studied. Many such etiological and management strategies have surfaced during the latest “coronavirus disease of 2019 (COVID-19) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 115 publications
1
4
0
Order By: Relevance
“…In our analyses, we found that sleep problems increased when the JSI worsened, and in addition, one of the COVID-19–related demands increased. Moreover, consistent with other research, 137 previous COVID-19 infection has been shown to be a risk factor for sleep problems. Of the other five health indicators, only psychosomatic complaints are predicted by a COVID-19 infection.…”
Section: Discussionsupporting
confidence: 91%
“…In our analyses, we found that sleep problems increased when the JSI worsened, and in addition, one of the COVID-19–related demands increased. Moreover, consistent with other research, 137 previous COVID-19 infection has been shown to be a risk factor for sleep problems. Of the other five health indicators, only psychosomatic complaints are predicted by a COVID-19 infection.…”
Section: Discussionsupporting
confidence: 91%
“…The proportion was significantly higher than in a matched non-COVID-19 control group [49]. Obesity, female sex, duration of hospital stay, and mental health concerns are identified risk factors of experiencing sleep disturbances due to COVID-19 [28,47,48].…”
Section: Introductionmentioning
confidence: 81%
“…A systematic review revealed that the people infected with SARS-CoV-2 showed a prevalence of sleep disturbances of 52,4% [46] even several months after hospital discharge [47]. Sleep disturbances are characterised as problems falling or staying asleep and are mostly leading to daytime fatigue [48]. Even after 2 years of COVID-19 the prevalence is still high with 31%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the SARS-CoV-2 threat, governmental authorities in various nations have instituted measures for social isolation to effectively manage the COVID-19 pandemic within their respective territories [27]. Subsequent investigations have revealed that such restrictions have been associated with adverse psychological effects, including anxiety and depression [28][29][30][31][32], sleep disturbances [33][34][35][36][37], and alterations in physical activity levels [36,38,39].…”
Section: Introductionmentioning
confidence: 99%